Sem studies regarding micromorphology of fruit, seed coat and pollen in genus hesperis l. (Brassicaceae) (Acta Horti Botanici Bucurestiensis, 2025)
The paper presents the micromorphological characteristics (SEM investigations) of fruits, seed coats and pollen grains of genus Hesperis in Austria. The siliquae are usually terete, glabrous and rarely with simple trichomes (subsp. nivea), straight or slightly curved. The seeds can present apical wings or not. The testa is reticulate and two main types were recognize based on seed coat surface, reticulate and ocellate-papillate. The pollen is tricolpate and exine is reticulate. The study revealed that palynological, fruit and seed micromorphological characteristics are significant in the taxonomy of the genus. An original dichotomic key for Hesperis species in Austria (H. matronalis subsp. matronalis and subsp. nivea, H. sylvestris, H. tristis) based on micromorphological characteristics is provided.